Clinical profile and outcome of children with meningitis- a prospective observational study in tertiary health care centre in Chennai - M Jahnavi; Sandip; Vimal Vijayakumar; Devaraj; S Thangavelu; K Nedunchelian (Wolters Kluwer Medknow Publications, 2018)
Objective: To study the clinical profile of children admitted with meningitis Design: Prospective observational study Setting: Study was conducted in PICU of tertiary health care centre in Chennai Participants: All children less than 18 years of age with a diagnosis of meningitis for a two years period between 2017- 2018 were included in the study Methods: All children with suspected meningitis admitted in pediatric intensive care unit of the Institution from January 2017 to December 2018 were studied. The variables included were age, sex, religion, residence, nutritional status, etiology of meningitis, duration of hospital stay, requirement of mechanical ventilation. The status of the child at the time of presentation, presence of shock, bleeding manifestations, raised intra cranial tension, was noted. The presence of sequelae and treatment and follow up was also noted. The collected data were analyzed with suitable statistical methods. Statistical analysis: Data was entered into Microsoft excel data sheet and was analyzed using SPSS 22 version software. Categorical data was represented in the form of Frequencies and proportions. Chi-square test was used as test of significance for qualitative data. Continuous data was represented as mean and standard deviation .p value of <0.05 was considered as statistically significant. Results: A total of 4237 children were admitted in the hospital out of which 13 meningitis cases in the age group below eighteen years comprised the study population. 3 (23%) were infants, 4 (30.7%) were between 1- 3 years of age, remaining 6 were more than3 years of age. Among the cases, 5 (38.4%) children were male and 8 (61.5%) were female. Among them, majority were Hindu (75.42%) by religion and urban (58.11%) by residence. Majority were due to bacteria while 3 (23.07%) each were due to viral and tubercular meningitis. Out of them 1 (8%) child was undernourished who had tuberculous meningitis. Out of the 13 children who were admitted, only 7 (53.88%) children were completely immunized. The duration of hospital stay was more than 2 weeks for 6 (46.1%) children, out of whom 2 had tubercular meningitis. Antibiotics were given for all of them while 8 (61.5%) children were given steroids. 4 (30.7%) had features of raised Intra cranial tension, while none had features of shock or bleeding manifestation or thrombosis.2 (15.38%) children required mechanical ventilation. Out of the children,2 (15.38%) had sequelae in the form of hydrocephalus,2 (15.38%) had subdural abcess,1 (7.3%) facial nerve palsy and hydrocephalus and 1 (7.3%) had hemiparesis. CSF analysis was done for all of the children with meningitis, out of whom CSF PCR showed hemophilus influenza b for 3 (23.7%) children, Escherichia shigella for 1(7.3%) child, Pneumococcus species for 1(7.6%) child candida for 1 (8.3%) child, enterovirus and streptococcus bovis for 1 (8.3%) child each. Conclusion: Acute bacterial meningitis still remains a major cause of mortality and morbidity in children. Hemophilus influenza remains the main cause in pediatric age group.